The study on the inadequacy of PUSPAL Guideline and ways to improve it / Izzatul Farhanim Mohd Razali...[et al.] - Mohd Razali, Izzatul Farhanim; Odenan, Nor Aishah; Othman, Nur Hanisah; Muhammad Adil, Siti Hadijah (Faculty of Law, 2013)
PUSPAL Guideline provides the rules that must be followed by the foreign artists, crews, and organizer who wants to make any performance in this country. PUSPAL Guideline plays a very important role in the entertainment industry. However, the Guideline is not adequate in terms of the definition of certain terms such as 'concert' and etc., in terms of its enforcement which is uncertain, and also in terms of the sanction imposed to the party who breach the Guideline. This study is to determine the effectiveness of PUSPAL Guideline as well as the scattered laws applicable in this country. The researchers had conducted an interview with personnel from the Law Department of Majlis Perbandaran Subang Jaya (MPSJ) in gaining more information regarding the research topic. The researcher had also used online articles to support the arguments as there were not many cases available for this research topic. While doing this research, the researchers have found laws that are not applicable to each and every state in Malaysia. It is important for a single Act to govern all concert related laws. This is because entertainment industry in this country is growing rapidly. This would also affect the wealth and growth of the economy. Thus, the purpose of this study is to revise the Guideline and put all related law regarding entertainment industry, in one Act.